1 Learning to lead. (12th November 2018) - Davies, Emma; Apperley, Harry
Abstract : Effective clinical leadership is associated with improved patient outcomes and is essential for good patient care. Leadership and Management (L and M) competencies are in the Foundation Training Curriculum and are a recognised GMC requirement, however there is a significant lack of L and M training for foundation trainees. Results of a survey distributed to all trainees in the foundation school revealed only 16% had received teaching on L and M in healthcare as a trainee, 99% thought engagement in L and M would be important for their future career, and 97% would engage with L and M training if offered the opportunity. In light of these findings we delivered an interactive teaching session within the foundation teaching programme at our local trust. 83% agreed that they understood more about L and M within the NHS and felt more prepared to engage with L and M opportunities after the session. Expansion of the teaching session as a regional near-peer teaching programme is in progress. Implementation of L and M teaching in the foundation curriculum can address the lack of exposure at junior doctor level. The teaching will provide trainees with a grounding in L and M and encourage engagement in clinical leadership as a foundation trainee and senior clinician of the future.